2020
DOI: 10.1111/aab.12587
|View full text |Cite
|
Sign up to set email alerts
|

Vertical farming systems bring new considerations for pest and disease management

Abstract: Vertical farming is an emerging area of food production that aims to provide sustainable intensification of agriculture by maximising the obtainable yield per unit area of land. This approach commonly utilises stacked horizontal levels of crop growth in glasshouse or controlled environment (CE) facilities. Vertical farming has, however, received relatively little scientific investigation to date. Consequently, important factors such as economic feasibility, system design and optimisation of production methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…The enclosed system also enables the farm to achieve resilience to extreme events and easier control of pest and pathogens as compared to more traditional cultivation systems (Kozai, 2019). Nevertheless, it has also been suggested that when pest outbreaks take place in PFALs, their impact may be dramatic, due to the combined effects of the relative proximity of plants (both in vertical and horizontal dimensions), as well as the intense air circulation fluxes needed to guarantee environmental uniformity (Roberts et al, 2020).…”
Section: Vertical Farms With Artificial Lightingmentioning
confidence: 99%
“…The enclosed system also enables the farm to achieve resilience to extreme events and easier control of pest and pathogens as compared to more traditional cultivation systems (Kozai, 2019). Nevertheless, it has also been suggested that when pest outbreaks take place in PFALs, their impact may be dramatic, due to the combined effects of the relative proximity of plants (both in vertical and horizontal dimensions), as well as the intense air circulation fluxes needed to guarantee environmental uniformity (Roberts et al, 2020).…”
Section: Vertical Farms With Artificial Lightingmentioning
confidence: 99%
“…Research on indoor farming and vertical farming has been ongoing for several years and represents multiple topics and streams. A map produced by VOSviewer 26 of the research landscape of ideas based on the co-occurrence of keywords (eg, "vertical farming"; "indoor farming") appearing in Scopus is Research on indoor farming includes farm production capabilities, 12 profitability and economics, 18,27 pest and disease management, 28 building information modeling, 29 energy management, 23,30 sustainability, urban planning and food security, 3,9,14-16 plant science, 13 and smart farming. 11 An excellent source of knowledge on indoor farming and plant factories can be found in Kozai et al 8,9 Topics include the impact of indoor farms on urban areas, global case studies, energy and resource use, operating efficiencies, plant science, systems design, growing methods and materials, indoor production processes, measurement, automation, sustainability of indoor farms, and next-generation designs.…”
Section: Research On Indoor Farmingmentioning
confidence: 99%
“…For example, arthropod pests or plant diseases can be introduced into protected horticulture systems through accidental contamination due to human activity or incoming materials such as seeds and/or substrates in combination with inadequate phytosanitation protocols and/or poorly maintained glasshouse and vertical farming structures. [ 223 ] Disease and pests thrive in this environment, and can cause damage through herbivory and vector plant pathogens. One can use beneficial organisms to control unwanted pests, including certain types of bacteria and fungi, to control spider mites and other invaders by crowding them out, eating them, or releasing compounds toxic to the pest.…”
Section: Novel Materials Concepts For Urban Farmingmentioning
confidence: 99%